External debt sustainability and vulnerabilities: Evidence from a panel of 24 Asian countries and prospective analysis - Matthieu Llorca (Asian Development Bank Institute (ADBI), 2017)
The purpose of this empirical study is first to assess the external debt sustainability in a panel of 24 Asian emerging and developing countries divided into four sub-panels, namely the regions of Southeast Asia, Southwest Asia, Central Asia, and the Pacific over the period 1993-2014. We use the present-value methodology to determine whether a country satisfies its intertemporal external constraint, namely whether its external debt is sustainable in the long run. According to such methodology, we study the panel stationarity of external debt, current account, imports, and exports, then the cointegration between these two last variables. We employ unit root and cointegration tests, the first and second generation tests, to take into account cross-sectional dependence. Our findings imply that the external debt in our panel of 24 Asian emerging and developing countries is sustainable in the long run. Finally, we analyze the vulnerabilities, factors, and risks in the region due to different external debt criteria (the debt currency composition, share of the short-term external debt, amount of reserves, and debt service). We conclude this study by establishing different prospective scenarios on the Asian emerging and developing countries according to the degree of economic slowdown (i.e., a "soft" or "hard" landing) in the People's Republic of China.
Keywords: C33; F32; F34; O53; 330; Economics